Effect of weathering and stockpile design on physicochemical properties of an Indian thermal coal. Issue 3 (4th March 2022) - Nandi, Barun Kumar; Bhattacharya, Sumantra
ABSTRACT: Two different stockpiles, one loose and another compact, in the open air were formed using approximately 500 tons of less than 200 mm size run of mines thermal coal on a concrete floor. Coal samples from the stockpile were collected at 30 days interval (from June 2016 to May 2017) for analysis of various chemical properties: proximate analysis, ultimate analysis, gross calorific value (GCV), and various burning profile temperatures such as ignition temperature, peak temperature, and burnout temperature. Experimental results show that, due to weathering of coal, elemental carbon decreased from 43% to 37%, hydrogen decreased from 4% to 3%, and GCV decreased from 3, 769 to 3, 211 kcal/kg during 330 days of storage of coal in an open atmosphere. Ash content of coal increased from 34% to 42.5% due to loss of combustibles. Sulfur was found to increase from 0.25% to 0.60% during storage. Variation in combustion parameters signifies that weathering has a significant negative impact on coal combustion properties as coal becomes difficult to ignite. Economic analysis infers that due to weathering of coal, for generation of 10, 000 kcal heat, coal consumption may increase from 2.65 to 3.13 kg, while ash generation increases from 0.9 to 1.30 kg.